Transitioning to Post-Pandemic Learning Modes: A Study On Teachers' Perspectives Regarding Technology Utilization - Eka Darma Patni, Ni Luh Putu; Wisnu Wardani, Dewi Ayu (International Journal of Multidisciplinary Sciences, 2024)
The Covid-19 pandemic has brought a major shift toward educational system in Indonesia. The face to face interaction in classroom was forced to change in online classroom. Despite some major challenges in adapting to the new situation during the pandemic, recent studies have shown that teachers are getting used to it. After approximately two years of adaption to online learning, as the government of Indonesia officially declares that social distancing and restrictions to people’s activity is null and void. This means that teachers need to shift once again to offline instructional process. Even though the instructional process is shifting back, there is still unanswered questions regarding the readiness of the teacher to teach offline since many scholars state that it is impossible to leave the technology behind. This study employs a quantitative survey design to examine the readiness of teachers during the transition of learning process after pandemic from their perspective. There are 15 teachers involved in this study who have passed the criteria to be subjects of the study. The findings and discussion of this study is hoped to give contribution to the knowledge of continuous professional development, technological acceptance model, and technological and pedagogical content knowledge.